Pesan Dakwah Dalam Novel Bumi Cinta Karya Habiburrahman El Shirazy (Ananlisi Semiotik Roland Barthes) - Fajrina Margareth Viruliana (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2022)
This study is a qualitative study that is descriptive, using a semiotic approach from Roland Barthes to examine the signs of.da'wah messages contained in the novel Bumi Cinta. Data.collection techniques used with observationand documentation. Data analysis techniques using Roland Barthes' semiotic analysis. The results of this study reveal that the message of da'wah in this Earth of Love novel, namely: 1) The message of da'wah contained in the form of words or sentences such as the message of creed, sharia and morals. Such as faith in Allah, prayer and morality towards fellow human beings, 2) The meaning of denotation shows Ayyas a young man who has a strong faith, obeys worship. 3) The meaning of connotation indicates that Ayyas was a young man who had a strong faith, like a rock that was firmly entrenched in the heart of Ayyas. Although Ayyas felt that he had no fortress or weapons to keep his faith, Ayyas always prayed to God that he would be strong against him.It is concluded that the word or sentence contained in the novel Bumi Cinta indicates the existence of proselytizing messages that have the meaning of denotation and connotation.